The Composition and The Maturity Level of The beach seine’s catches Based on the Construction’s Aspect at the Pasir Putih Beach, District of South Bungus,Teluk Kabung,Padang, West Sumatra. - Muhammad Rifqi; Nofrizal Nofrizal; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Thisresearchwasconducted inAugust2018 atPasirPutihBeach,DistrictofSouthBungus,TelukKabung,Padang,WestSumatra.Thepurposeofthisstudyistofindoutthecompositionandthematuritylevelofthebeachseine’scatches.Themethod in this research is survey’s method with Data analysis based on the analysis of the composition and the level of maturity of the catch.Basedonthisresearch,therewere10speciesofcatchessuchas:Stolephorussp, Leiognathusdussumieri, Upeneusmoiluccensi,Mastigoteuthisflammea, Xiphias gadius, Mene maculata, Nemitarus nematophorus, Caranxignobilis,Selaruides leptolepis and Geres punctatus. There were 142 species of fish that were observed in the Gonad maturity level which 89 species of them are male and 53 of them are female.Keyword:beach seine, composition of catc, maturity level